PATTERN RECOGNITION THEORY AND NEUROCOMPUTERS - M. M. Tatur (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The new approach to use of key statements of pattern recognition theory for the parallel problem oriented processors design is presented. The tasks of classification, clusterization and association are considered from point of view of parallel processor architecture unification. As a final result the domestic neuron like computer prototype is announced.